Mitral valve infective endocarditis as a manifestation of disseminatedCryptococcus neoformans infection: a case report - Flores-Alamos, Oyuky (2024)
Infective endocarditis is a disease that affects mainly the endocardial surface of the heart and cardiac valves (native or prosthetic). The main risk factors for developing infective endocarditis are male sex, older age, intracardiac shunts, prosthetic valves, rheumatic, and congenital heart disease, intracardiac devices, intravenous drugs use, immunosuppression, and hemodialysis. Streptococci and Staphylococci spp. have been the most frequent isolated organisms. On the other hand, the most common fungal organism in infective endocarditis is Candida albicans (24-46%), followed by Aspergillus spp. (25%), and a few cases by Cryptococcus neoformans, which are associated with higher rate of mortality. This case provides an interesting case of Cryptococcus neoformans native valve infective endocarditis in a young woman with stage IV chronic kidney disease and severe malnutrition.